Regulating reciprocal distances: House construction projects as inverse governmentality in Maputo, Mozambique - Morten Nielsen (Danish Institute for International Studies (DIIS), 2009)
Although reciprocal relationships with neighbours and local-level civil servants are of paramount importance to people living on the outskirts of Maputo, Mozambique, they also harbour destructive potentials. In an unstable urban environment built on a presumption of malice, it is consequently important only to reveal what needs to be seen while concealing those facets which might awaken unwanted desires. This working paper examines how residents in a periurban area seek to position themselves at appropriate distances to important but potentially dangerous others. It is argued that house-building constitutes a potent medium for proportioning viable distances so that reciprocal exchanges can be realized without being harmed by presumed greedy and envious others. In particular, the paper explores how house-builders imitate urban norms which state and municipality claim to be using but which they are incapable of implementing. Through such processes of inverse governmentality, illegal occupancy acquires a form of pragmatic legitimacy when appearing to materialise state-defined urban norms.
Keywords: 330; Wohneigentum; Nachbarschaftsökonomie; Stadt; Soziale Norm; Maputo; Mosambik